Neuroinflammation: Microglia and T Cells Get Ready to Tango - Schetters, Sjoerd T. T.; Gomez-Nicola, Diego; Garcia-Vallejo, Juan J.; Van Kooyk, Yvette (Frontiers in Immunology, 2018)
In recent years, many paradigms concerning central nervous system (CNS) immunology have been challenged and shifted, including the discovery of CNS-draining lymphatic vessels, the origin and functional diversity of microglia, the impact of T cells on CNS immunological homeostasis and the role of neuroinflammation in neurodegenerative diseases. In parallel, antigen presentation outside the CNS has revealed the vital role of antigen presenting cells in maintaining tolerance towards self-proteins, thwarting auto-immunity. Here, we review recent findings that unite these shifted paradigms of microglial functioning, antigen presentation and CNS-directed T cell activation, focusing on common neurodegenerative diseases. It provides an important update on CNS adaptive immunity, novel targets and a concept of the microglia T-cell equilibrium.